Description and phylogenetic position of Plagiolemma distortum sp. nov., a new raphid diatom (Bacillariophyceae) from French coastal waters. Issue 1 (2nd January 2018) - Nézan, Elisabeth; Bilien, Gwenael; Boulben, Sylviane; Mertens, Kenneth Neil; Chomérat, Nicolas
Abstract : A new marine raphid diatom, Plagiolemma distortum Nézan, sp. nov. is described from plankton samples from the Atlantic Ocean, south Brittany (north-western France), where it was regularly observed, but never in high abundances. Cells have an unusual and complex shape under light microscopy (LM) depending on their position and orientation. The two valves are highly vaulted and narrow in width (transapical axis). Cells contain four complexly lobed plastids and a variable number of refractive granules without particular localization. In addition, capsules containing motile cells were observed. Ultrastructural details of the frustules were investigated using scanning electron microscopy (SEM). The girdle bands are simple. Each valve possesses a sigmoid raphe raised on a ridge and ending in external large openings with elaborate internal helictoglossae. Moreover, each valve displays outer slit-like foramina and inner rounded hymenes, external terminal minute holes (micropyles) arranged in a row at the poles. In addition, on each valve face, one to several short transverse median costae are observed, terminating far away from the valve edges. Morphological comparisons with closely related taxa show that P. distortum is a new species. A video clip of a moving cell is provided for better understanding of the cell shape. The formation and function of capsules are discussed as well as the species habitat. A phylogenetic study, based on nuclear small subunit (SSU) ribosomal DNA (rDNA) sequence data, which includes new sequences relative to Plagiolemma and Plagiotropis, was performed. Furthermore, some morphological details observed with SEM are included in an emended generic diagnosis of Plagiolemma .